2001
DOI: 10.1634/stemcells.19-4-313
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 3 Improves the Ex Vivo Expansion of Primitive Human Cord Blood Progenitor Cells and Maintains the Engraftment Potential of SCID Repopulating Cells

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
2
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 44 publications
2
32
2
1
Order By: Relevance
“…cells up to more than 75-and 18-fold in just 6 days of culture, respectively. Such level of expansion in only 6 days of culture compares advantageously with other protocol previously reported with SFM (Rossmanith et al 2001;Ueda et al 2000;Araki et al 2006) although protocols with longer expansion periods are as expected associated with greater overall level of cell expansion (Pineault and Abu-Khader 2015). Moreover, phenotypic analyses showed that the productions of immature CB subpopulations such as CD34 ?…”
Section: Discussionsupporting
confidence: 69%
“…cells up to more than 75-and 18-fold in just 6 days of culture, respectively. Such level of expansion in only 6 days of culture compares advantageously with other protocol previously reported with SFM (Rossmanith et al 2001;Ueda et al 2000;Araki et al 2006) although protocols with longer expansion periods are as expected associated with greater overall level of cell expansion (Pineault and Abu-Khader 2015). Moreover, phenotypic analyses showed that the productions of immature CB subpopulations such as CD34 ?…”
Section: Discussionsupporting
confidence: 69%
“…The results are compared with those obtained in cultures stimulated with SCF and IL-3, a combination known to stimulate expansion of progenitor cells from neonatal CD34 + cells. [25][26][27] Very few, if any, CB-LDC survived 10-12 days of serumdeprived cultures in the absence of growth factors 19,25 or when stimulated with only one of the cytokines investigated (results not shown). SCF and IL-3 induced an increase in the number of total nucleated cells and of CFC in these cultures (average FI ¼ 3.672.13 and 5.5272.04, Po0.01, respectively) ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…To reproduce conditions that most likely will be used in clinical settings, the cultures were seeded with the mononuclear fraction of CB, although in selected experiments purified neonatal T cells were cultured under the same conditions for comparison. The cultures were stimulated with the early multilineage cytokine SCF in combination with either IL-3, a factor known to stimulate proliferation of CD34 + cells Ex Vivo T-cell amplification M Sanchez et al purified from either neonatal [25][26][27] or adult 33 specimens, or with IL-7, IL-4 and IL-2, cytokines known for their activity on lymphoid cells. 34 IL-7 provides nonredundant signals for T-and B-cell development and is produced by the same stromal cells that produce SCF in the fetal liver, in the adult bone marrow and in the thymus, 14,35 where the highest The Vb gene rearrangements were analyzed in parallel before and after culture for direct comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of mononuclear cells and the subsequent immunomagnetic selection of CD34 + or CD34 + CD38 -cells were performed as previously described. 40 Culture and analysis of leukemic progenitor cells. CD34 + cells were maintained in X-Vivo (Lonza) supplemented with 10% FCS (Hyclone), 1% L-Glutamine (Invitrogen), interleukin-3, thrombopoietin (25 ng/mL each), stem cell factor and Flt-3 ligand (50 ng/mL each, Peprotech) for seven days.…”
Section: Methodsmentioning
confidence: 99%
“…Flow cytometry was performed as previously described. 40 For the The expression data were evaluated using the ΔΔCT method. 42 Analysis of AML1/ETO and PLZF/RARα in the spleen cells was performed in reference laboratories in Frankfurt (Dr. Heike Pfeifer, Department of Medicine II, Johann Wolfgang Goethe-University) and Munich (PD Dr. Susanne Schnittger) by quantitative real-time PCR (qRT-PCR) using GAPDH as a housekeeping gene, as previously described.…”
Section: Methodsmentioning
confidence: 99%